Women’s Language Features Used by The Female Main Character on It Ends with Us Novel - Arta, Putu Deta Yunia Hapsari; Matradewi, Ni Ketut Widhiarcani; Putra, I Komang Sumaryana (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This study entitled Women’s Language Feature Used by The Female Main Character on It Ends Us novel aims to explore the women’s language features and the function that was used by the female main character, Lily Bloom from Colleen Hoover’s Novel ‘It Ends with Us.’ A documentation method was applied as the method of collecting data, to analyze the data, a descriptive qualitative was applied, formal method used to present the analysis. The female lead character's conversation in the movie